Long - Term Relationship Between Misery Index And Stock Market: The Colombian Case (2013)
Essays on Growth, Development and Finance includes selected papers on special topics in economics that were presented at various conferences organized by the Athens Institute for Education and Research in 2010, 2011 and 2012. More than 250 participants attended the three conferences on Economics alone from Europe, North America, South America, Africa, Australia, and Asia. The conferences’ papers covered a variety of topics in economics ranging from Macroeconomics, International Economics, Financial Economics.